2016
DOI: 10.1189/jlb.1a0415-164r
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-7 promotes human regulatory T cell development at the CD4+CD8+ double-positive thymocyte stage

Abstract: Although mature human FOXP3(+) regulatory T cells are CD127 (IL-7Rα) negative, CD4(+)CD8(+) FOXP3(+) thymocytes express relatively high levels of CD127 and are responsive to IL-7. However, the role of IL-7 in human regulatory T cell development is poorly known. We show that at the CD4(+)CD8(+) stage, FOXP3(+) thymocytes are highly susceptible to apoptosis, and IL-7 selectively rescues them from death, leading to an increased frequency of FOXP3(+) cells. IL-7 also promotes the development of regulatory T cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Figure 2 show representative pictures of the different groups analyzed. The stimulation observed could be due to the production of IL-7 which is involved in the ontogeny and maturation of T lymphocytes [26][27][28]. These studies confirm that yogurt supplementation not only improves thymus weight as we mentioned before, but also significantly improves the histology of this organ (Figure 2).…”
Section: Resultssupporting
confidence: 78%
“…Figure 2 show representative pictures of the different groups analyzed. The stimulation observed could be due to the production of IL-7 which is involved in the ontogeny and maturation of T lymphocytes [26][27][28]. These studies confirm that yogurt supplementation not only improves thymus weight as we mentioned before, but also significantly improves the histology of this organ (Figure 2).…”
Section: Resultssupporting
confidence: 78%
“…We have previously shown that IL‐7 protects DP CD25 + thymocytes from apoptosis, and analysis of Annexin V/propidium iodide staining showed that IL‐2 has the same effect, as well. In these experiments, the surface marker CD25 instead of FOXP3 was used, since permeabilization of the cells is not compatible with detection of apoptotic cells.…”
Section: Resultsmentioning
confidence: 77%
“…We have previously reported that IL‐7 promotes the Treg phenotype and protects FOXP3 + cells from apoptosis at the DP stage in the human thymus . To see whether the effects of IL‐7 on BCL‐2 were similar to IL‐2, we analysed BCL‐2 expression in the thymocyte culture with and without IL‐7.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations